UMP focuses on sustainable development to convey Malaysia Madani idea - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 16 March 2023 - The Chairman of the Board of Directors of Universiti Malaysia Pahang (UMP), Tan Sri Dato’ Sri Dr. Abdul Aziz Abdul Rahman delivered a Public Lecture titled ‘UMP Madani’ which focused on the Malaysia Madani Idea by implementing a comprehensive work movement to realise the university’s desire to achieve the aspirations of the Ministry of Higher Education (MOHE) in line with the national agenda.